Peran Pendidikan Pancasila Dalam Membangun Karakter Mahasiswa di Era Globalisasi Saat Ini - Alya Alya; Dina Handayani; Dyana Lestari Harefa; Hannyfa Amira Salwa; Melany Putri; Muethia Arifah; Nia Damai Putri; Fazli Rachman (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
. Pancasila education plays a very important role in efforts to achieve the national mission to shape the nation's personality amid the challenges of the current globalization era. The value of character towards Pancasila Education is increasingly fading, especially among the younger generation such as students and college students. The purpose of this study is to provide a clear picture in building the character of special students in the current era of globalization. The research method used is a literature study method sourced from journals, the next method is a qualitative method with data collection techniques through observation. The results of this study indicate that Pancasila education has an important role in building and developing the character of students so that later it will produce a young generation that is noble and critical. The impact of the phenomenon of globalization can actually cause the decline of the nation's identity, so it is increasingly important to include Pancasila education in the curriculum. This research contributes to raising awareness of the importance of Pancasila education as a means to strengthen and maintain national identity in the face of increasing globalization.